Contemporary hero in audiovisual narrative. The case of Walter White and "Breaking Bad" - Castro Balbuena, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This article uses narrative theory to search the «lost hero» or the classic hero in audiovisual narrative. The first step of this research will be the definition of contemporary hero according to academic sources. Secondly, I will analyse the evolutive status of the hero in audiovisual narrative, looking for possible coincidences between literary hero and audiovisual hero. All these theories will lead to a concrete character analysis, Walter White, protagonist of televisual fiction Breaking Bad.
Keywords: contemporary hero; audiovisual narrative; character; Walter White; Breaking Bad